2007
DOI: 10.1111/j.1751-1097.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 5‐Fluorouracil Dideoxyribonucleoside Monophosphate

Abstract: 5-Fluorouracil is an artificial nucleobase analog of thymine and uracil, with a substituent in the 5-position that has a mass similar to the methyl group in thymine, but very different electronic, steric and vibrational coupling properties. UVC irradiation of 5-fluorouracil dideoxyribonucleoside monophosphate (dXpdX) is examined here with mass spectrometry and UV-Vis absorption spectroscopy and is compared to the UV photochemistry of other pyrimidine dideoxyribonucleoside monophosphates. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…The latter undergoes further thermal dehydration to form a thermally stable 5,5′-diuridynyl adduct. Furthermore, on the basis of the above observations and previous reports, the formation of cyclobutane-type adducts can now be assigned as a general feature of the photochemistry of 5-halogenouracil ( F U, Cl U and Br U) compounds.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The latter undergoes further thermal dehydration to form a thermally stable 5,5′-diuridynyl adduct. Furthermore, on the basis of the above observations and previous reports, the formation of cyclobutane-type adducts can now be assigned as a general feature of the photochemistry of 5-halogenouracil ( F U, Cl U and Br U) compounds.…”
supporting
confidence: 62%
“…It has been demonstrated that the adduct is thermally unstable, undergoing cyclobutane ring cleavage with concomitant hydrolysis to form the 5-hydroxyuracil analogue of the starting dinucleotide model . Furthermore, the formation of cyclobutane-type adducts was also observed for other 5-halogenouracil compounds, namely, in the case of thymidylyl-(3′-5′)-2′-deoxy-5-fluorouridine monophosphate and 5-chlorouracil containing dinucleotide model compounds and 5-bromo-2′-deoxyuridine in frozen aqueous solution …”
mentioning
confidence: 98%
“…The value for the photochemical component of the reorganization energy for 9-MeA (66%) is lower than for 5-fluorouracil (81%) and thymine (73%), , but it is more than that reported for cytosine and uracil . Therefore, less of cytosine’s and uracil’s reorganization energy are directed along the photochemical coordinate, compared to 9-MeA, 5-fluorouracil and thymine.…”
Section: Discussionmentioning
confidence: 66%
“…The resonance Raman spectra obtained for the related analogue of these two, 5-FU, shows intensity that are more similar to thymine than uracil, thereby supporting the mass barrier hypothesis. 23 The value for the photochemical component of the reorganization energy for 9-MeA (66%) is lower than for 5-fluorouracil (81%) and thymine (73%), 23,56 but it is more than that reported for cytosine and uracil. 22 Therefore, less of cytosine's and uracil's reorganization energy are directed along the photochemical coordinate, compared to 9-MeA, 5-fluorouracil and thymine.…”
Section: ' Resultsmentioning
confidence: 81%
See 1 more Smart Citation